2009
DOI: 10.1310/tsr1602-122
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Web-Based Caregiver Intervention on the Reasons Stroke Survivors Use Health Care Services During the First Year Post Treatment

Abstract: This study informs professionals about the care and needs of stroke survivors and provides direction for education and supportive interactions with caregivers and survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…PTs and OTs in this study suggested that the integration of ICT solutions in the rehabilitation process could potentially accommodate some of the stroke survivors' need for continuing access and communication with health professionals after discharge from acute or subacute care. These findings are in line with other studies, that have found ICT solutions to have the potential to create a more extensive follow-up after discharge from acute care, thus extending the rehabilitation period [23,26,32], in addition to being an important safety net and assurance during the initial period of returning home after discharge [28], thus generating feeling of connectedness with the health care system. Furthermore, a more extended follow-up after discharge seems to be motivating for both the stroke survivor and the health professionals [23,49,50,55] and can improve participation in daily life after stroke [56].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…PTs and OTs in this study suggested that the integration of ICT solutions in the rehabilitation process could potentially accommodate some of the stroke survivors' need for continuing access and communication with health professionals after discharge from acute or subacute care. These findings are in line with other studies, that have found ICT solutions to have the potential to create a more extensive follow-up after discharge from acute care, thus extending the rehabilitation period [23,26,32], in addition to being an important safety net and assurance during the initial period of returning home after discharge [28], thus generating feeling of connectedness with the health care system. Furthermore, a more extended follow-up after discharge seems to be motivating for both the stroke survivor and the health professionals [23,49,50,55] and can improve participation in daily life after stroke [56].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, a more extended follow-up after discharge seems to be motivating for both the stroke survivor and the health professionals [23,49,50,55] and can improve participation in daily life after stroke [56]. Several studies have shown that mobile phone based interventions after discharge, varying from 3-14 phone calls within six months post-stroke, in addition to one personal visit from health professionals, can reduce stroke survivors' and significant others' depression and burden, and improve their health and satisfaction with the rehabilitation process [21,26,28,32,49,57].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study about the support of Web-based training prepared for caregivers of stroke survivors, it was found that the interaction between the patient and caregiver became stronger; caregivers improved patient care through the information they received from the Web site, and survival period of patients increased. 18 Responses to the statement ''Videos and explanations enabled me to obtain information, I generally like it'' expressed by caregivers regarding the Web site and their responses on the questionnaire evaluating site efficiency revealed that short videos, convenience of exercises to perform at home without much effort, and simplified information were most appreciated. No opinion was declared for the question of the disliked features.…”
Section: Distribution Of Responses Of Caregivers Regarding Their Levementioning
confidence: 99%
“…However, there are a limited number of studies focusing on the effectiveness of Web-based training and support for family caregivers of stroke survivors. 9,[17][18][19] …”
mentioning
confidence: 99%